VIB1, a Link between Glucose Signaling and Carbon Catabolite Repression, Is Essential for Plant Cell Wall Degradation by Neurospora crassa - Xiong, Yi; Sun, Jianping; Glass, N. Louise (PLoS genetics, 2014)
Filamentous fungi that thrive on plant biomass are the major producers of hydrolytic enzymes used to decompose lignocellulose for biofuel production. Although induction of cellulases is regulated at the transcriptional level, how filamentous fungi sense and signal carbon-limited conditions to coordinate cell metabolism and regulate cellulolytic enzyme production is not well characterized. By screening a transcription factor deletion set in the filamentous fungus Neurospora crassa for mutants unable to grow on cellulosic materials, we identified a role for the transcription factor, VIB1, as essential for cellulose utilization. VIB1 does not directly regulate hydrolytic enzyme gene expression or function in cellulosic inducer signaling/processing, but affects the expression level of an essential regulator of hydrolytic enzyme genes, CLR2. Transcriptional profiling of a Δvib-1 mutant suggests that it has an improper expression of genes functioning in metabolism and energy and a deregulation of carbon catabolite repression (CCR). By characterizing new genes, we demonstrate that the transcription factor, COL26, is critical for intracellular glucose sensing/metabolism and plays a role in CCR by negatively regulating cre-1 expression. Deletion of the major player in CCR, cre-1, or a deletion of col-26, did not rescue the growth of Δvib-1 on cellulose. However, the synergistic effect of the Δcre-1; Δcol-26 mutations circumvented the requirement of VIB1 for cellulase gene expression, enzyme secretion and cellulose deconstruction. Our findings support a function of VIB1 in repressing both glucose signaling and CCR under carbon-limited conditions, thus enabling a proper cellular response for plant biomass deconstruction and utilization.